Persepsi Nasabah Terhadap Layanan Digital Bank BCA: Studi Kualitatif dan Implikasinya dalam Pengembangan Strategi Perbankan Digital - Pratiwi Musa, Kartika Septiary (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aims to explore customer perceptions of BCA Bank's digital services and their implications for digital banking strategy development. Using a qualitative approach, in-depth interviews were conducted with active customers using BCA Bank's digital services, while document content analysis was also performed to gain comprehensive understanding. Findings indicate that key factors influencing customer perceptions include user interface quality, system reliability, security, ease of use, and availability of additional features. BCA Bank can utilize these findings to enhance user experience, improve their digital services, and strengthen competitive advantage in the evolving digital banking market.